DOES PAYMENT METHOD OF MERGERS AND ACQUISITIONS MATTER? AN EXAMINATION OF THE MEDICAL INDUSTRY IN CHINA - YE, Chengkui; YUAN, Hao; LU, Pingan (Journal of Advanced Studies in Finance; Vol 5 No 1 (2014): JASF Volume V, Issue 1(9), Summer, 2014, 2014)
This study examines the impact of payment method and share of large shareholder on individual stocks after mergers and acquisitions. A research framework based on the Capital Asset Pricing Model (CAPM) is developed to identify factors of merger and acquisition that would affect stock return of the medical industry in China using transaction value, price-earnings ratio, debt asset ratio total asset as control variables. The results reveal that PE ratio, percentage of large shareholder ownership and pure cash payment method take positive effect on 30-day cumulative abnormal returns. Mergers and acquisition settled in cash has positive effect, so is share of large shareholders.